Meningkatkan Kemandirian Belajar Anak Panti Asuhan Melalui Konseling Individu dengan Teknik Penguatan Positif - Anggia Septiani; Nuraida Nuraida; Zhila Jannati (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2019)
This study aims to determine individual counseling with positive reinforcement techniques in increasing children's learning independence at the Fathurrahman Al Barokah Orphanage in Palembang and to find out the description of learning independence after counseling. The research subjects in this study were three teenagers at the Fathurrahman Al-Barokah Orphanage in Palembang who had low learning independence. This type of research is field research. Data collection methods used are observation, interviews, and documentation. The data analysis of this research is data reduction, data presentation, and verification/conclusion. The results of this study indicate that (1) the learning description of the children at the Fathurrahman Al-Barokah orphanage in Palembang is that the orphanage children experience low learning independence, such as not being able to learn independently and still need the help of others. (2) The implementation of individual counseling with positive reinforcement techniques by choosing a social reinforcer, in the form of compliments, smiles, statements, applause and thumbs up. Rewards are given continuously every time the target behavior appears, and (3) There is a change in the description of learning independence, namely an increase in the learning independence of children at the Fathurrahman Al-Barokah Orphanage in Palembang.